Clinical characteristics of Kawasaki disease in adolescents - Xiaoliang Liu (SAGE Publishing, 2021)
Objective Studies focusing on Kawasaki disease (KD) in adolescents are lacking in Southwest China. We systematically summarized the clinical characteristics of KD in adolescents to improve pediatricians’ recognition of this condition. Methods The clinical data of patients with adolescent-onset KD in our center were retrospectively analyzed. The patients were divided into Group A (n = 7), whose first hospitalization was at our hospital, and Group B (n = 10), who were transferred from their local hospital or community health center. Results Seventeen patients with adolescent-onset KD were identified (constituent ratio of 0.8%). Seven patients had an intermittent fever for >10 days. The incidence of incomplete KD was 52.9%. These patients had a high incidence of other atypical clinical manifestations. Fifteen patients were initially misdiagnosed with other infectious diseases. Although the incidence of typical KD was higher in Group B, the overall misdiagnosis rate at the initial stages was higher and the average fever duration on arrival and before IVIG administration were much longer in Group B than A. Conclusions KD in adolescents was frequently misdiagnosed, which might be associated with its atypical, diverse clinical features and pediatricians’ poor recognition. Pediatricians must be aware of the possibility of KD in adolescents.